PENGGUNAAN MEDIA KOMPUTER DALAM PERKULIAHAN MEKANIKA BERDASARKAN MODEL PEMBELAJARAN PEMECAHAN MASALAH BERBASIS KONSEP - Padri, I Made (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2002)
This paper is the result of tried out of innovation in Mechanics course with problem solving teaching-learning model based on concept by using computer, conducted in DUE Like project at Physics Department of FPMIPA UPI in academic year 2002/2003.In principle, the objective of this innovation is to improve the student role (student centred) in attending Mechanics course, which in turn will improve the quality of the student learning result.Concretely, the main point of the implementation of this learning model in Mechanics course includes:Group discussion in finding and solving problem, based on problem and concept structure that presented in handout.Presentation the result of group discussion to get comments from all students.Strengthening and completingÂ the discussion result by lecturer using computer media.Tutorial to guide students in finishing some problems taken from textbook.Derived from the average score and the percent of the success student in each examination, it can be concluded that the usage of problem solving teaching- learning model based on concept by using computer media, significantly can improve the student learning result, compared to the result of the same course when it is just using OHP. While from the answer of the questioner which just returned by 50% students, generally stated that the teaching-learning model and the media used in Mechanics lecture are good enough, even though there is an impression that the students found difficulty in learning alone which based on textbook and handout. It happened, may be, because of the previous learning style which is teacher-centred.